Implementation of Risk Management Systems In Investment banks - Malyavantam, Yashas Sathyaprakash (2009)
Investment banks are changing fast. In past years investment banks played a safe role. In recent years and at present the financial crisis has led to credit crunch. The investment banks are facing a lot of risks in the recent years. The risk management is playing a significant role in the present business world to overcome the risks. The risk management system takes different steps to control any kind of risk faced. So, I would like to investigate the Risk management systems of the Investment banks. The dissertation will include the way the investments banks implement the risk management systems to overcome the different kinds of risks. I want to consider some top four investment banks globally and they are: Goldman Sachs, JP Morgan, Merrill Lynch and Lehman Brothers. This piece of work will include all the above banks risk management systems and their implementation of it.